THE CADETS' ENGLISH COMPETENCE AND THEIR COMMUNICATION PROBLEMS IN THE INTERNATIONAL ONBOARD TRAINING: A CASE STUDY AT POLITEKNIK ILMU PELAYARAN MAKASSAR - Palayukan, Novianty; Asnur; Fathir, Muh; Hasyari, Mutmainnah (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
In the international onboard training, the cadets must be able to have good and effective English communication. It is due to the operational communication on the ship that must be delivered in English. However, several cadets possessed some communication problems when delivering English communication during the operation of the ship. This study aimed to investigate (1) the English competence of Indonesian seafaring cadets, (2) the communication challenges they faced during international onboard training, and (3) the proposed solutions to these challenges. The research employed a mixed-methods approach at Politeknik Ilmu Pelayaran Makassar (PIP Makassar), involving 29 cadets who recently completed international onboard training. The data were gathered through documentation, open-ended questionnaires, and in-depth interviews. English competence was assessed using descriptive statistical analysis, while communication problems and solutions were analyzed using the interactive model of Miles, Huberman, and Saldana (2014). Findings showed that cadets encountered physical (unclear radio conversations), linguistic (use of substandard English), psychological (lack of confidence), and cultural barriers (different communication styles), despite generally good English competence. Proposed solutions include habituating radio conversations, improving confidence, and adapting globally to various linguistic and cultural communication styles.